Cover Picture: Electrochemically Induced Diels‐Alder Reaction: An Overview (Chem. Rec. 04/2020. Issue 4 (14th April 2020) - Heravi, Majid M.; Zadsirjan, Vahideh; Kouhestanian, Elham; AlimadadiJani, Behnoush
Abstract : The cover picture shows a graphical image of electrochemically induced Diels‐Alder reaction. The use of electricity instead of stoichiometric amounts of oxidant or reducing agents in organic synthesis is appealing for economic, ecological and selective reasons. See the Personal Account by M. M. Heravi, V. Zadsirjan et al. (DOI: 10.1002/tcr.201900018 ).